Design of DCU Smart Lighting for Public Streetlights in Medan City - Batubara, Febrin Aulia; Anugrahwaty, Rina (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
Currently, Medan City is developing a public streetlight project along the highways of Medan City. The Medan city government has spent billions to fix this. The construction of these public streetlights also consumes the city's electricity resources. Efficiency measures are needed to reduce the use of electricity for public streetlights. We propose this research using smart lighting technology. This device will detect human and vehicle movements, time settings, and step dimming that allows dynamic lighting and dimming. This technology also allows for communication from one device to another, such as if a pedestrian or car is detected, then the surrounding streetlights will turn on. This device will be equipped with PIR sensors, ultrasonic sensors, and light sensors. With the development of Internet of Things technology currently, it is expected to help control remotely and have an integrated system. The control and monitoring system is connected via the internet. The parameters to be controlled are the presence of humans, vehicles, and lighting, and all these parameters can be monitored with web-based and Android applications. Based on the above studies, this research will design a public streetlight system using a Data Control Unit (DCU) to facilitate the control system, and this device will be integrated with sensors such as human sensors (PIR), light sensors, and ultrasonic sensors. The system is in the form of smart lighting that can be monitored remotely, such as whether lights will be bright or dim if there are road users and vehicles, and each streetlamp will be connected to each other wirelessly.